1998
DOI: 10.1183/09031936.98.12040799
|View full text |Cite
|
Sign up to set email alerts
|

Effect of salbutamol on dynamic hyperinflation in chronic obstructive pulmonary disease patients

Abstract: Bronchodilating agents are commonly used in patients with chronic obstructive pulmonary disease (COPD) to reduce airway obstruction [1]. Although many COPD patients may obtain substantial increase in airflow after inhalation of bronchodilators [2], one-third of them do not show significant acute spirometric changes [3]. It is a common tenet, however, that improvements in symptoms and exercise capacity may occur even in the absence of spirometric improvement [4]. Such findings are frequent in patients with rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
128
1
14

Year Published

2000
2000
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 190 publications
(153 citation statements)
references
References 30 publications
10
128
1
14
Order By: Relevance
“…This provides a reasonable mechanistic explanation for the close association between resting IC and exercise tolerance in FL patients. Assessment of IC has already been shown to provide useful information on the effects of surgical treatment [25] and bronchodilators [26] on hyperinflation in COPD patients. Recently, it has also been shown that in COPD patients the increase in IC after anticholinergic therapy best reflected the improvements in exercise endurance and dyspnoea [27].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This provides a reasonable mechanistic explanation for the close association between resting IC and exercise tolerance in FL patients. Assessment of IC has already been shown to provide useful information on the effects of surgical treatment [25] and bronchodilators [26] on hyperinflation in COPD patients. Recently, it has also been shown that in COPD patients the increase in IC after anticholinergic therapy best reflected the improvements in exercise endurance and dyspnoea [27].…”
Section: Discussionmentioning
confidence: 99%
“…Assessment of FL may also provide a useful guide for rehabilitation in COPD patients: in patients without FL, rehabilitation based on exercise should be particularly beneficial, while in patients with FL administration of bronchodilators and inspiratory muscle training should be preferable in order to decrease the prevailing hyperinflation [26,27] and to increase the working capacity of the inspiratory muscles [28,29].…”
Section: Discussionmentioning
confidence: 99%
“…Assessment of tidal FL was made using: 1) the NEP technique [2,4] and 2) the "conventional" method of superimposition of tidal with maximal expiratory flow/volume (V9/V) curves [11]. In this case, volume was measured with the body plethysmograph to avoid errors due to thoracic gas compression [18].…”
Section: Expiratory Flow Limitationmentioning
confidence: 99%
“…Using the negative expiratory pressure (NEP) technique, it has been shown that in patients with chronic obstructive pulmonary disease (COPD) there is a high prevalence of expiratory flow limitation (FL) during resting breathing [1][2][3][4]. The presence of tidal FL promotes dynamic pulmonary hyperinflation (DH) and intrinsic positive end-expiratory pressure, with a concomitant increase of inspiratory work, impairment of inspiratory muscle function, and adverse effects on haemodynamics [5].…”
mentioning
confidence: 99%
“…La evaluación de los cambios de volumen pulmonar no requiere de equipos sofisticados, ya que con un simple espirómetro es posible medir la capacidad vital lenta (CVL), la capacidad vital forzada (CVF) y la capacidad inspiratoria. Se desconoce cuál es la magnitud de los cambios de volumen y cuántos pacientes podrían ser catalogados como respondedores frente a los broncodilatadores, basados sólo en los cambios de volumen, ya que los trabajos que han explorado esta aproximación adolecen de limitaciones entre las que destacan: el carácter retrospectivo de un estudio 10 , no existiendo la certeza de que los pacientes estudiados fueran todos portadores de EPOC; el empleo de dosis muy elevadas de salbutamol (5 mg) 11 , lo que no permite establecer si los resultados son aplicables a la práctica diaria; la exclusión de pacientes que mejoran los flujos espiratorios (VEF 1 ) frente a los broncodilatadores 12 ; y el análisis de grupos pequeños de pacientes 13,14 . De acuerdo con estos antecedentes, el propósito del presente trabajo fue estudiar si la administración de 200 µg de salbutamol, dosis que se emplea habitualmente para evaluar la reversibilidad en la prueba espirométrica, produce mayores cambios de volumen pulmonar que del VEF 1 en pacientes portadores de EPOC con distinto grado de severidad de la obstrucción y en etapa estable de la enfermedad.…”
unclassified